Development and evaluation of a rapid enzymatic hydrolysis test method to assess the biodegradability of organic waste - Wagland, Stuart T. (Cranfield University, 2008)
The amount of biodegradable municipal waste (BMW) that can be disposed of in a landfill must be reduced, in accordance with the landfill allowance trading scheme (LATS) in England and Scotland (LAS in Wales). Biodegradability test methods are used to monitor the quantities of BMW diverted by waste treatment processes. This research has outlined the requirements for timescale improvements on the currently used methods. The rapid (<24 h) enzymatic hydrolysis test (EHT) has been developed and the relationship of this with the long-term BM100 test has been compared with that of the established DR4 method. A range of untreated and treated organic waste materials taken from a number of treatment processes, and samples taken over a period of 9 months from a single treatment facility were analysed using each test method. The EHT is completed within 1 day, compared with 4 days for the current DR4 method, and was shown to possess a stronger correlation with the long- term BM100 test. This finding indicated the suitability of the EHT as an alternative short-term test method. A humic substance extraction step was added to the EHT procedure, which was expected to provide a more accurate estimation of sample biodegradability. This technique was, however, found to be unsuitable for use in a short-term test method based on the results presented, although further understanding of the processes involved in the EHT has been discussed. This thesis presents a new biodegradability test method, which has been developed, applied and evaluated. The processes of the EHT have been investigated, understood and discussed. Further developments are suggested based on the findings and observations throughout the thesis.